Exploration of the stakeholders' views on the liberalization of provisionally registered pharmacists (PRP) training / Abdul Qaiyum Abdul Razak - Abdul Razak, Abdul Qaiyum (2014)
Background: A new policy was implemented by the Malaysian government that liberalizes the training of Provisionally Registered Pharmacists (PRPs) in Malaysia. The reason behind the implementation is because the placement for PRPs has been reducing due to saturation as the number of pharmacy graduates are increasing. Since this issue is very new, not many studies had been done to explore the readiness, benefits and the barriers to the stakeholders in becoming training centres for PRPs. Objectives: This study explores the readiness of the stakeholders to become training centres for PRPs. This study also explores the barriers and the benefits of this liberalization policy to the stakeholders. Methods: Participants from community pharmacies and pharmaceutical industries were identified and approached from February to June 2014 through snowball sampling. In depth interviews were conducted and all face-to-face interviews were audio recorded and transcribed verbatim. For industrial pharmacists, phones interview were conducted, audio recorded and then transcribed verbatim. The transcripts were analyzed using framework analysis. Results: Three mam themes that emerged are: the readiness of the stakeholders, perceived benefits of the liberalization policy and perceived disadvantages of the liberalization policy. In term of readiness, the pharmaceutical industry is generally ready to train the PRPs but this is not the case for community pharmacies. The perceived benefits of liberalization mainly revolves around the increase in qualified human resources in private sector while the disadvantages are mainly on the issues of financial barriers, business secret and confidentiality as well as the quality of PRPs themselves.